Photodegradation of Malachite Green by Immobilization of Titanium Dioxide on Glass Plates - Lee, Pei-Wen; Ong, Siew-Teng; Hung, Yung-Tse; Lee, Siew-Ling (Asian Journal of Chemistry, 2012)
The effects of pH, contact time, initial dye concentration, numbers of dip coating, light sources and repetitive usage of dip-coated TiO2 were studied in batch experiments in order to investigate the photodegradation efficiency of malachite green in aqueous solution by using titanium dioxide, TiO2 immobilized on glass plates. The photodegradation of malachite green was found to be more effective at lower initial dye concentration. Kinetic studies showed good correlation coefficient for a pseudo-first order kinetic model. The removal of malachite green was dependent on the TiO2 loading where the percentage removal of malachite green was 92.15, 94.28 and 98.43 % for 5, 10 and 15 number of TiO2 dip-coating, respectively. Among the three light sources used, sunlight possessed the highest removal efficiency with 100 % of removal of dye in 6 h of irradiation. The degradation of malachite green was enhanced in basic solution compared with acidic solution due to the amphoteric property of TiO2. The decolourization efficiency was found to be decreased after each repetitive usage of dip-coated TiO2 glass plates. However, the immobilized TiO2 still displayed a good performance in the removal of malachite green.